2020
DOI: 10.1055/s-0039-3402767
|View full text |Cite
|
Sign up to set email alerts
|

Fat Grafting for Facial Rejuvenation

Abstract: For optimal results, facial rejuvenation procedures should address both the tissue laxity and volume deflation associated with facial aging. The lift-and-fill face lift, in which fat grafting provides volumetric rejuvenation to the face while surgical lift effectively repositions and removes ptotic and redundant tissue, has revolutionized the plastic surgeon's approach to the aged face. An understanding of the intricate anatomy of distinct facial fat compartments and a systematic method to assess areas of fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 32 publications
(50 reference statements)
1
36
0
1
Order By: Relevance
“…Fat transplantation, which can achieve the effects of adjusting the proportions of facial contours, restoring tissue volume, and improving skin texture (3)(4)(5)(6)(7)(8), is currently a common surgical method in plastic surgery. With the wide application of fat grafting technology in plastic surgery or other specialties, complications, such as edema, infection, hematoma, calcification, granuloma formation, fat necrosis, and vascular embolism (9)(10)(11)(12), present significant challenges for plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Fat transplantation, which can achieve the effects of adjusting the proportions of facial contours, restoring tissue volume, and improving skin texture (3)(4)(5)(6)(7)(8), is currently a common surgical method in plastic surgery. With the wide application of fat grafting technology in plastic surgery or other specialties, complications, such as edema, infection, hematoma, calcification, granuloma formation, fat necrosis, and vascular embolism (9)(10)(11)(12), present significant challenges for plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…27 Fat grafting can also be performed in conjunction with the face or neck lift to volumize certain facial regions, thus contributing to a more youthful appearance. [28][29][30] Fat grafting serves as a good option as it is readily available, inexpensive, and easily reproducible. 31 By incorporating the "lift" and "fill" principle, it has been demonstrated that the surgeon can both recontour the face and address volume deflation of the different fat compartments.…”
Section: Preoperative Planningmentioning
confidence: 99%
“…31 By incorporating the "lift" and "fill" principle, it has been demonstrated that the surgeon can both recontour the face and address volume deflation of the different fat compartments. 29,30…”
Section: Preoperative Planningmentioning
confidence: 99%
“…De acordo com Cotofana et al (2016), o conhecimento da organização complexa dos tecidos de suporte, retenção e revestimento merecem atenção especial para o aperfeiçoamento de procedimentos rejuvenescedores. Dentre as estruturas, os ligamentos de retenção da face (LRF) merecem destaque, posto que o envelhecimento promove diminuição de sua função, enfraquecimento da sustentação e, consequentemente, o torna como um dos fatores preponderantes para observação clínica da face envelhecida (Alghoul & Codner, 2013, Schultz et al, 2020.…”
Section: Introductionunclassified